Human Knowledge and the Divine in Islamic Philosophy - Atfaliyah, Hodiqotul; Rujikartawi, Erdi; Wasehudin, Wasehudin; Gunawan, Agus; Pandriyani, Yosie Kristin (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study aims to analyze the Islamic philosophical tradition in understanding knowledge and humanity’s path toward God as the core of the spiritual and intellectual journey within the Islamic intellectual tradition. This study focuses on the thought of key figures such as Al-Farabi, Ibn Sina, Al-Ghazali, and Mulla Sadra, who have made significant contributions to the concepts of epistemology, metaphysics, and the process of human self-perfection. This research employs a qualitative method with a content analysis design. The units of analysis consist of texts from Islamic philosophical works. Data were collected through literature review and documentation. Analysis was conducted using Miles and Huberman’s thematic analysis aided by NVivo, through the stages of coding, categorization, data presentation, and drawing conclusions. The results indicate that the tradition of Islamic philosophy views knowledge as a gradual process involving the harmony of reason, intuition, and the purification of the soul. The human journey toward God is understood as a process of self-knowledge (ma’rifat al-nafs), the enhancement of intellectual capacity, and moral transformation that culminates in an existential closeness to God. This research is beneficial for enriching the study of Islamic philosophy, providing a comprehensive understanding of the integration of reason and spirituality, and serving as a foundation for the development of character and spiritual education within the context of modern learning.